Numerical analysis of the effect of nitrogen and oxygen admixtures on the chemistry of an argon plasma jet operating at atmospheric pressure. (3rd March 2015) - Gaens, W Van; Iseni, S; Schmidt-Bleker, A; Weltmann, K-D; Reuter, S; Bogaerts, A
Abstract: In this paper we study the cold atmospheric pressure plasma jet, called kinpen, operating in Ar with different admixture fractions up to 1% pure, and + . Moreover, the device is operating with a gas curtain of dry air. The absolute net production rates of the biologically active ozone ( ) and nitrogen dioxide ( ) species are measured in the far effluent by quantum cascade laser absorption spectroscopy in the mid-infrared. Additionally, a zero-dimensional semi-empirical reaction kinetics model is used to calculate the net production rates of these reactive molecules, which are compared to the experimental data. The latter model is applied throughout the entire plasma jet, starting already within the device itself. Very good qualitative and even quantitative agreement between the calculated and measured data is demonstrated. The numerical model thus yields very useful information about the chemical pathways of both the and the generation. It is shown that the production of these species can be manipulated by up to one order of magnitude by varying the amount of admixture or the admixture type, since this affects the electron kinetics significantly at these low concentration levels.